Don't just do something, stand there - Jerome R Hoffman; Michael S Wilkes (Sociedade Brasileira de Medicina de Família e Comunidade, 2015)
Imagine a (hypothetical) screening test which, done in a population of average risk, saves one person from dying from cancer out of every 10,000 people screened.  Imagine as well that every one of those 10,000 pays a price in terms of time and money spent, as well as discomfort, and that some or even many of them will also have to deal with increased anxiety, repeat testing, biopsies, and in a few cases, surgery. Finally, a few will have serious adverse effects like infection or organ failure.